KAJIAN â€˜URF PADA PENOLAKAN SERTIFIKASI HALAL MUI TERHADAP PENAMAAN PRODUK BERLABEL SETAN - Faiza, Siti Nur (Universitas Muhammadiyah Surabaya, 2021)
This research is the result of field research to analyze the 'urf study on the rejection of the MUI halal certification of naming â€œdevil noodle productsâ€. In conducting research, the author uses qualitative methods by using field data and complemented by secondary data to strengthen the analysis that comes from previous research, books, journals, decrees, and others. Then, uses descriptive analysis techniques to analyse. Noodle devil is one of the spicy culinary foods that has a lot of customers but in its business journey this product did not get approval to get the halal label of the East Java MUI because the devil's name does not match